Reação de genótipos de feijoeiro comum a Fusarium oxysporum f. sp. phaseoli, Macrophomina phaseolina e Xanthomonas campestris pv. phaseoli - Maringoni, Antonio Carlos [UNESP]; Lauretti, Renato Luis Bertoni [UNESP] (FapUNIFESP (SciELO), 1999)
The behavior of dry bean (Phaseolus vulgaris L.) genotypes PI 150414, PI 163117, PI 175829 white, PI 175829 purple, PI 175858, PI 197687, A 417, A 420, A 429, Xan 160, Xan 161, WISHBR 40, and IAC Carioca inoculated with Fusarium oxysporum f. sp. phaseoli, Macrophomina phaseolina, and Xanthomonas campestris pv. phaseoli was evaluated under greenhouse condition. The bean genotypes Xan 160, PI 150414, A 417, PI 175829 purple, Xan 161, A 420, PI 163117, and PI 175829 white were resistant to F. oxysporum f. sp. phaseoli, and only PI 155829 white had a good level of resistance to M. phaseolina. All bean genotypes were susceptible to Feij-4 strain, and only Xan 161 had some level of leaf resistance to Feij-41 strain of X. campestris pv. phaseoli.

Foi avaliado no presente trabalho o comportamento dos genótipos de feijoeiro (Phaseolus vulgaris L.) PI 150414, PI 163117, PI 175829 branco, PI 175829 roxo, PI 175858, PI 197687, A 417, A 420, A 429, Xan 160, Xan 161, WISHBR 40 e IAC Carioca inoculados com Fusarium oxysporum f. sp. phaseoli, Macrophomina phaseolina e Xanthomonas campestris pv. phaseoli, sob condições de telado/casa de vegetação. Verificou-se que os genótipos Xan 160, PI 150414, A 417, PI 175829 roxo, Xan 161, A 420, PI 163117 e PI 175829 branco foram resistentes a F. oxysporum f. sp. phaseoli e somente o PI 175829 branco apresentou bom nível de resistência a M. phaseolina. Com relação ao comportamento desses genótipos a X. campestris pv. phaseoli, eles foram altamente suscetíveis ao isolado Feij-4 e apenas o genótipo Xan 161 apresentou nível moderado de resistência foliar ao isolado Feij-41.
Behavior of dry bean genotypes to Fusarium oxysporum f. sp. phaseoli, Macrophomina phaseolina, and Xanthomonas campestris pv. phaseoli
Keywords: Ashy stem blight; Common bacterial blight; Disease resistance; Fusarium yellows; Phaseolus vulgaris; Bacteria (microorganisms); Fusarium oxysporum f. sp. phaseoli; Fusarium sp.; Macrophomina phaseolina; Phaseolus (angiosperm); Xanthomonas; Xanthomonas campestris pv. phaseoli